A Controllable Gate Effect in Cobalt(II) Organic Frameworks by Reversible Structure Transformations1. Issue 44 (13th September 2013) - Chen, Qiang; Chang, Ze; Song, Wei‐Chao; Song, Han; Song, Hai‐Bin; Hu, Tong‐Liang; Bu, Xian‐He
<x xml:space="preserve">Abstract</x> With H2O or NH3 stimuli, the blue cobalt‐based metal–organic framework (MOF) BP can reversibly transform to red RP. The removal/recovery of terephthalate ligands accompanied by the transformation leads to a gate effect, which allows the encapsulation and release of small solvent molecules under certain conditions. This is the first example of topology transformation from a self‐penetrating to interpenetrating net in 3D MOFs.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>